Gradients of flow regulation shape community structures of stream fishes and insects within a catchment subject to typhoon events - Nukazawa, Kei; Shirasaka, Kodai; Kajiwara, Shinsuke; Saito, Tsuyoshi; Irie, Mitsuteru; Suzuki, Yoshihiro (The Science of the total environment, 2020)
Alterations in natural flow regimes caused by dams can significantly alter the aquatic habitats of stream organisms. However, few studies have characterized flow regulation to assess its impacts on stream fauna in the context of interannually variable extreme floods. This study aims to understand the variation in stream animals along flow regulation gradients due to hydropower dams in a catchment experiencing typhoons. We observed freshwater fishes and stream insects at fully regulated sites (receiving residual flow), moderately regulated sites (receiving hydropower outflow), and nonregulated site (tributary) in the Mimi River catchment in southern Japan, in summer and winter from 2010 to 2018. We computed indicators of hydrologic alteration (IHA) in each calendar/water (July to June) year from 2007 to 2017 and selected subsets of IHA based on principal component analysis (PCA) and variance inflation factor. The largest variance was mainly explained by minimum discharge levels (e.g., 30-day annual minimum) and flow variability among IHAs, distinguishing the moderately regulated and nonregulated sites from fully regulated sites because of residual flow and suppressed high pulses in the fully regulated sites. Generalized additive models revealed that annual maxima of specific discharge were most significant predictors of fish and insect metrics while its effects were generally inconsistent between summer and winter. Non-metric multidimensional scaling revealed that insect communities were clustered into the regulation extents in both seasons. The differences in winter fauna between the regulated and nonregulated sites, characterized by Ephemeroptera-Plecoptera-Trichoptera abundance, were associated with maximum discharge and high pulse numbers. Fish community variation did not correspond to flow regime gradients. Our findings on mechanistic ecohydrological consequences of various flow regulations, supported by long-term observations, will be useful for river managers attempting to compensate for alterations in flow regime and ecological integrity. [Display omitted] •Little is known about impacts of flow regulation with typhoons on stream animals.•Long-term flow and organism data at a catchment subject to typhoons were used.•Flow regimes were characterized to assess relevant impacts on insects and fish.•Insect community was sensitive to flow regimes and typhoons.•Eco-hydrological consequences of flow regulation will be useful to river managers.